2017
DOI: 10.3390/molecules22081200
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomics-Guided Exploration of the Phytochemical Constituents of Vernonia fastigiata with the Aid of Pressurized Hot Water Extraction and Liquid Chromatography-Mass Spectrometry

Abstract: Vernonia fastigiata is a multi-purpose nutraceutical plant with interesting biological properties. However, very little is known about its phytochemical composition and, thus the need for its phytochemical characterization. In the current study, an environmentally friendly method, pressurized hot water extraction (PHWE), was used to extract metabolites from the leaves of V. fastigiata at various temperatures (50 °C, 100 °C, 150 °C and 200 °C). Ultra-high performance liquid chromatography-quadrupole time of fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The detected abundant molecular ion signals [M‐H] − for flavonol‐ O ‐glycosylated ( 30‐32 , 40–43 , 45 , 46 , 51 ) (Table ) were in agreement with ESI‐MS/MS data . Additionally, to the confirmation by high resolution data from LC‐ESI/TOF MS analysis, compounds ( 30 ), ( 31 ), ( 32 ), and ( 41 ) had its structure fully confirmed by NMR in previous work .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The detected abundant molecular ion signals [M‐H] − for flavonol‐ O ‐glycosylated ( 30‐32 , 40–43 , 45 , 46 , 51 ) (Table ) were in agreement with ESI‐MS/MS data . Additionally, to the confirmation by high resolution data from LC‐ESI/TOF MS analysis, compounds ( 30 ), ( 31 ), ( 32 ), and ( 41 ) had its structure fully confirmed by NMR in previous work .…”
Section: Resultssupporting
confidence: 85%
“…Fragments at m/z 353, 191, 179, and 173 were significant for the identification of caffeoyl quinic acid derivatives. Dihydrocaffeoyl quinic acid derivatives were identified by fragment‐ions at m/z 355, 337, and 323 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to mention that the same glycosylation patterns have been noted with other similar flavonoids such as kaempferol and isorhamnetin [40]. This phenomenon of diversification can be said to be species/genus specific because other plants such as Vernonia fastigiata diversify their flavonoid composition by swapping sugar positions [42]. For instance, V. fastigiata produces two isobaric molecules, quercetin-3-O-hexoside-O-pentoside and quercetin-3-O-pentoside-O-hexoside, both appearing at m/z 595.1245 but at different retention times, again indicating differences in polarities [42].…”
Section: Phytochemicals In Moringa Oleiferamentioning
confidence: 90%
“…This phenomenon of diversification can be said to be species/genus specific because other plants such as Vernonia fastigiata diversify their flavonoid composition by swapping sugar positions [42]. For instance, V. fastigiata produces two isobaric molecules, quercetin-3-O-hexoside-O-pentoside and quercetin-3-O-pentoside-O-hexoside, both appearing at m/z 595.1245 but at different retention times, again indicating differences in polarities [42]. As such, the above is an indication that advanced analytical techniques need to be developed in order to fully cover the flavonoid composition of the plant.…”
Section: Phytochemicals In Moringa Oleiferamentioning
confidence: 99%
“…Clovamide, a minor compound present in the antioxidant polyphenolic fraction of Theobroma cacao L. at ppm levels, was originally identified in red clover, and was found also in many other plants. [27][28][29][30][31] Its expression can be induced by specific treatment, such as jasmonic acid, 32 and, finally, the molecule can be synthetized. 16,[33][34][35] Herein we have demonstrated that clovamide treatment of hCPCs could decrease the levels of ROS accumulated within the CPCs after an oxidative stress, which are then responsible for cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%